MINDFULNESS DENGAN PERILAKU PERAN SAKIT PADA PASIEN PASCA STROKE - Andi Dian Diarfah; Andi Weri Sompa (Journal Medical Universitas muhammadiyah Makassar, 2019)
Stroke is a common cause of disability and has a large impact on an individual's life. Stroke recovery is very individual and requires a long process. Family support is not enough to give effect to the recovery of post-stroke sufferers, the mindfulness of post-stroke sufferers themselves to recover is also needed. The purpose was determined the relationship between mindfulness with sick role behavior in post-stroke patients with. The subjects were 110 people with characteristics aged 30-65 years. The instruments of this study were the Applied Mindfulness Process Scale (AMPS) and Barcylas Sick Role Process Inventory (BSRPI). The technique of Mediated Multiple Regression was the data analysis. The results showed there was a correlation between mindfulness and sick role behavior (β = 0.51, p 0.05).